A recognition-gated azobenzene photoswitch. (29th March 2018) - Ouyang, Yu; Yuan, Ziyong; Wang, Jiaobing
Abstract : Complexation of metal ion controls the photoswitching of a push–pull azobenzene derivative. Abstract : We describe a push–pull azobenzene derivative whose photoswitching can be regulated by molecular recognition. Complexation of the tetra-amide receptor with a Hg 2+ ion blocks an intramolecular charge transfer (ICT) excited state, thereby gating the population of a π–π* excited state, which is responsible for the photoswitching.